Pengaruh Debt To Equity Ratio Dan Non Performing Loan Terhadap Return Saham Emiten Bursa Efek Indonesia Subsektor Perbankan - Maman Sulaeman; Hasan Fahmi Kusnandar; Gun Gun Gunawan; Meiyanti Widyaningrum; Sufia Widi Kasetyaningsih (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to determine the effect of debt to equity ratio (DER) and non performing loan (NPL) to stock returns of issuers of Indonesia Stock Exchange banking subsector. The method used in this research is descriptive quantitative. The population in this study as many as 43 issuers Indonesia Stock Exchange banking subsector but who qualified samples only 7 emiten. Technique of collecting data is done through secondary data that is financial report of emiten become sample. While to analyze the data obtained used path analysis. The results showed that DER and NPL have a very strong effect on stock return that is equal to 81,4%. Based on the path analysis of the effect of DER on ROA of 50.5% and the effect of NPL to ROA of 30.9%.